Genetic Modifiers of Oral Nicotine Consumption in Chrna5 Null Mutant Mice - Meyers, Erin; Werner, Zachary; Wichman, David; Mathews, Hunter L.; Radcliffe, Richard A.; Nadeau, Joseph H.; Stitzel, Jerry A. (Frontiers in Psychiatry, 2021)
The gene CHRNA5 is strongly associated with the level of nicotine consumption in humans and manipulation of the expression or function of Chrna5 similarly alters nicotine consumption in rodents. In both humans and rodents, reduced or complete loss of function of Chrna5 leads to increased nicotine consumption. However, the mechanism through which decreased function of Chrna5 increases nicotine intake is not well understood. Towards a better understanding of how loss of function of Chrna5 increases nicotine consumption, we have initiated efforts to identify genetic modifiers of Chrna5 deletion-dependent oral nicotine consumption in mice. For this, we introgressed the Chrna5 knockout (KO) mutation onto a panel of C57BL/6J-Chr#A/J/NAJ chromosome substitution strains (CSS) and measured oral nicotine consumption in 18 CSS and C57BL/6 mice homozygous for the Chrna5 KO allele as well as their Chrna5 wild type littermates. As expected, nicotine consumption was significantly increased in Chrna5 KO mice relative to Chrna5 wild type mice on a C57BL/6 background. Among the CSS homozygous for the Chrna5 KO allele, several exhibited altered nicotine consumption relative to C57BL/6 Chrna5 KO mice. Sex-independent modifiers were detected in CSS possessing A/J chromosomes 5 and 11 and a male-specific modifier was found on chromosome 15. In all cases nicotine consumption was reduced in the CSS Chrna5 KO mice relative to C57BL/6 Chrna5 KO mice and consumption in the CSS KO mice was indistinguishable from their wild type littermates. Nicotine consumption was also reduced in both Chrna5 KO and wild type CSS mice possessing A/J chromosome 1 and increased in both KO and wild type chromosome 17 CSS relative to KO and wild type C57BL/6 mice. These results demonstrate the presence of several genetic modifiers of nicotine consumption in Chrna5 KO mice as well as identify loci that may affect nicotine consumption independent of Chrna5 genotype. Identification of the genes that underlie the altered nicotine consumption may provide novel insight into the mechanism through which Chrna5 deletion increases nicotine consumption and, more generally, a better appreciation of the neurobiology of nicotine intake.